1H‐ and 13C‐NMR spectroscopic study of chemical equilibria in the system acetaldehyde + water. Issue 1 (30th September 2014) - Scheithauer, Andreas; von Harbou, Erik; Hasse, Hans; Grützner, Thomas; Rijksen, Christiaan; Zollinger, Daniel; Thiel, Werner R.
<x xml:space="preserve">Abstract</x> Acetaldehyde is an important intermediate in the chemical industry and often used in mixtures with water. These mixtures are reactive multicomponent systems, as acetaldehyde forms oligomers with water. Quantitative studies of the resulting speciation are scarce in the literature and limited to the formation of the smallest oligomer, ethane‐1, 1‐diol. Therefore, in the present work, a comprehensive study of chemical equilibria in mixtures of acetaldehyde and water was carried out by quantitative 1H‐ and 13C‐NMR spectroscopy. The study covers temperatures between 275 and 338 K and overall acetaldehyde mole fractions between about 0.05 and 0.95 mol/mol. The peak assignment is given for both the 1H‐ and 13C‐NMR spectra. From the speciation data, obtained from the peak area fractions, numbers for the chemical equilibrium constants of the oligomer formation are obtained and a correlation is presented. © 2014 American Institute of Chemical Engineers AIChE J, 61: 177–187, 2015